MILK CONSUMPTION BEHAVIOR IN HOUSEHOLD HAVING CHILDREN IN GROWING AGE IN YOGYAKARTA SPECIAL PROVINCE - Widiati, R.; Kusumastuti, T.A.; Andarwati, S. (Diponegoro University, 2013)
The objectives of this study were to determine socio-economic factors that influence milkconsumption and propensity to routine milk consuming in a household that have children in growing agein both urban and rural area of Yogyakarta Special Province. Numbers of respondent were 122households in urban area and 102 in rural area. Survey method was used to collect data usingquestionnaires presented to respondents. The data were analyzed quantitatively using a log linearmultiple regression and binomial logistic regression models. Results of the research showed that milkprice and mother’s education background were highly significant factors in determining the milkconsumption expenditure. Individually, the income was not significant factor. Furthermore, urbanhousehold group with higher mother’s education and household income were different significantly withthe rural one. A number of children who were less than 12 years old had significantly greater propensityto consume milk routinely. The program to increase milk consumption for children in growing ageshould be focused on improving the knowledge of mothers in low income communities especially inrural areas accompanied with required skills to get employment opportunities and extra cash income.